2013
DOI: 10.5606/ehc.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and scanning electron microscopy confirm that bone microstructure is similar in osteopenic and osteoporotic patients

Abstract: Amaç: Daha önce "ışık mikroskopi çalışması" ile elde edilen "Femur boyun kırığı olan osteopenik ve osteoporotik hastalarda kemik mikromimarisi benzerdir" bulgusunu ki, önemli ve yenidir, teyit etmek amaçlandı. Hastalar ve yöntemler: Düşük enerjili travma sonrası femur proksimal uç kırığı nedeniyle başvuran 14 hasta (5 erkek, 9 kadın) çalışmaya alındı (ışık mikroskopi çalışmasına katılan hastalar). Hastalar kemik mineral yoğunluğu (KMY) ölçümlerine göre osteopenik (n=7, ort. yaş 69 yıl; dağılım 63-74 yıl) ve os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The mean time to union was 17 weeks (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in the PFLP group ( Figure 1) and 18 weeks (range 16-32) in the ABP group (Figure 2). The mean ASA score was 2.7 and 3.1 in the PFLP and ABP groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean time to union was 17 weeks (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in the PFLP group ( Figure 1) and 18 weeks (range 16-32) in the ABP group (Figure 2). The mean ASA score was 2.7 and 3.1 in the PFLP and ABP groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…osteoporotic fractures. [28] However, further studies consisting of homogeneous subgroup types with similar degree of osteoporotic bone can reveal more accurate results on indications and effectiveness of PFLP and ABP.…”
Section: Discussionmentioning
confidence: 99%
“…One fetus diagnosed as PLH [14] had generalized defective mineralization of the bones including the skull and multiple fractures due to low activity of serum alkaline phosphatase enzyme. In parental history, consanguineous marriage and one more baby with diagnosed PLH were noted (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] There are reports indicating that long-term alendronate use may cause an increased susceptibility to fractures. [3,4] Also, recent reports have suggested that a potential complication may be delayed union after atypical femoral fracture stabilization in patients taking long-term bisphosphonate.…”
mentioning
confidence: 99%